2006
DOI: 10.1080/09511920600622056
|View full text |Cite
|
Sign up to set email alerts
|

Run-time interpretation of STEP-NC: implementation and performance

Abstract: This paper describes an experiment in building and running two STEP-NC interpreters for milling operations: one using ISO 14649, the other using AP 238 of ISO 10303. Both use STEP part 21 exchange files as input and call low-level machine control functions. Both include tool path generators and have sufficient functionality to execute the first example program at the end of part 11 of ISO 14649. The objectives and results were: (1) to determine if ISO 14649 and AP 238 contain sufficient information to run a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…By providing the high-level information to machining systems, STEP-NC will not only eliminate the costly and inefficient process of data postprocessing, it will also establish a unified environment for the exchange of information between product design, machining process planning and inspections. It enables the realization of a closed, STEP-NC based machining process chain with data feedback and a consolidated data structure at each level [22,23]. Industrial use of STEP/STEP-NC has shown evidence of significant cost saving, higher quality, and reduced time-to-market.…”
Section: Step/step-ncmentioning
confidence: 97%
“…By providing the high-level information to machining systems, STEP-NC will not only eliminate the costly and inefficient process of data postprocessing, it will also establish a unified environment for the exchange of information between product design, machining process planning and inspections. It enables the realization of a closed, STEP-NC based machining process chain with data feedback and a consolidated data structure at each level [22,23]. Industrial use of STEP/STEP-NC has shown evidence of significant cost saving, higher quality, and reduced time-to-market.…”
Section: Step/step-ncmentioning
confidence: 97%
“…Using currently available software tools, ISO 14649 can be interpreted significantly faster (Kramer et al 2006). A detailed indepth study with explanations of the differences between G&M code and STEP-NC and in what way is the STEP-NC better than G&M code has provided a better insight into the capabilities of both standards.…”
Section: Discussionmentioning
confidence: 97%
“…The "what-to-do" information maintains its generic nature until the last moment when a Fig. 4 IDEF0 diagram for detailed design of optimisation module CAM system populates the process plan with native manufacturing information in order to generate a specific "howto-do" process plan (Wang et al 2007;Xu et al 2006;Kramer et al 2006). Generic machining tools and generic cutting tools conform to the data defined by ISO 14649 Part 111 (ISO 14649-111: 2001).…”
Section: Optimisation Modulementioning
confidence: 99%